Experimental Evidence of EU Issue Voting - Pannico, Roberto (2023)
The chapter focuses on the consequences of EU politicization on electoral behaviour. It investigates whether and under which conditions EU citizens consider their EU positions when casting a vote in national elections. First, we use a conjoint experiment to investigate the magnitude of EU issue voting in six EU countries. This design allows us to cope with possible endogeneity problems while simulating the complexity of the task faced by real voters. Second, we link the media data presented in the previous chapters to the experiment’s results to explore how EU issue voting is influenced by the informational context. The main results and several robustness checks show that in almost all the countries analysed respondents are more likely to vote for a party that shares their own position on the EU than for a party that does not. However, it seems that not all types of voter-party incongruence have the same electoral consequences. Finally, the findings also suggest a relationship between media content and EU issue voting.